The Influence of Workload, Work Culture, and Job Satisfaction on Organizational Citizenship Behaviour at PT Bank Sumut - Syafitri, Suci Indah (Journal of International Conference Proceedings, 2023)
Organizational Citizenship Behavior (OCB) is important to company success because in general organizations cannot rely solely on formal job descriptions to predict all of their organizational behavior. The importance of researching OCB in banking companies is because banking companies have intense competition so there are many things that employees must do to work according to the target. Therefore, it can be said that the contribution of OCB is a contributor that will benefit in the future. This research was conducted on PT Bank Sumut employees totaling 160 non-management employees. Data analysis uses the F test and multiple linear regression analysis. Research results show that workload has a significant impact on OCB work culture has a significant impact on OCB and job satisfaction has a significant impact on OCB. OCB is also affected by work culture and job satisfaction. The magnitude of the influence of workload, work culture and job satisfaction in influencing OCB is 64%. This study aims to determine the effect of workload, work culture and job satisfaction on OCB.